2009
DOI: 10.1126/science.1168750
|View full text |Cite
|
Sign up to set email alerts
|

Structure of P-Glycoprotein Reveals a Molecular Basis for Poly-Specific Drug Binding

Abstract: P-glycoprotein (Pgp) detoxifies cells by exporting hundreds of chemically unrelated toxins but has been implicated in multidrug resistance in the treatment of cancers. Substrate promiscuity is a hallmark of Pgp activity, thus a structural description of polyspecific drug-binding is important for the rational design of anticancer drugs and MDR inhibitors. The x-ray structure of apo-Pgp at 3.8 Å reveals an internal cavity of ∼6,000 Å 3 with a 30 Å separation of the two nucleotide binding domains (NBD). Two addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

102
2,027
5
15

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,794 publications
(2,149 citation statements)
references
References 32 publications
102
2,027
5
15
Order By: Relevance
“…Finally, using PEGylation of the cavity and competition with MccJ25, we showed that MccJ25 is entering the cavity by the cytoplasmic side of the inward‐open McjD rather than a lateral membrane opening as proposed for other ABC transporters (Aller et al , 2009). This is the first evidence that McjD adopts an inward‐open conformation for peptide binding.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Finally, using PEGylation of the cavity and competition with MccJ25, we showed that MccJ25 is entering the cavity by the cytoplasmic side of the inward‐open McjD rather than a lateral membrane opening as proposed for other ABC transporters (Aller et al , 2009). This is the first evidence that McjD adopts an inward‐open conformation for peptide binding.…”
Section: Discussionsupporting
confidence: 60%
“…From these studies, it is unclear how the hydrophobic peptide MccJ25 enters the McjD cavity. We sought to answer the following question: (i) does MccJ25 enter through a lateral opening from inside the membrane as suggested for other ABC transporters (Aller et al , 2009), since McjD is found in an occluded conformation, or (ii) does it enter through an inward‐open form of McjD? Therefore, we performed competition assays by pre‐incubating McjD N134C, I138C and T298C mutant ISOVs with 1 mM MccJ25 followed by the addition of 1 mM mPEG10k.…”
Section: Resultsmentioning
confidence: 99%
“…p0345 Recently, relatively detailed atomic level crystal structures have become available for the homologues of human ABCB1, the Caenorhabditis elegans, and the mouse Abcb1 proteins (Aller et al, 2009;Jin, Oldham, Zhang, & Chen, 2012). Thus, proper localization of the amino acids within and outside the transmembrane helices can be estimated.…”
Section: P0340mentioning
confidence: 99%
“…All the computational methods discussed here, such as MD simulation or in silico docking, require high-resolution 3D structure of the protein under investigation. While murine Abcb1 has been crystallized in an apo state (Aller et al, 2009), and sufficient homology models can be built for its ATP-bound conformation (Globisch et al, 2008;O'Mara & Tieleman, 2007;Pajeva, Globisch, & Wiese, 2009), structural or homology models of human ABCG2 are insufficient for in silico studies because of the low-resolution structure information (cryoelectron microscopy, >5 Å ) (Rosenberg et al, 2010) and the very low (<20%) sequence similarity of the TMD with any existing ABC structure that could be applied as a possible template. s0110 5.1.…”
Section: Article In Pressmentioning
confidence: 99%
“…10 Directed mutagenesis performed on the different TMs of MDR1 revealed the implication of different residues on the TMs 1, 5, 6, 11 and 12 in substrates recognition (Figure 1). However, the interaction domains of MDR1 with its different substrates are variable and depend on both their nature and conformation.…”
Section: Introductionmentioning
confidence: 99%